Women and the Heart: Webcast April 16 2024 - Miguel A. Quiñones; Valeria E. Duarte; Christopher Hobday; Saurabh Rajpal; Carla P. Rodriguez-Monserrate; Karla Kurrelmeyer; Gladys Velarde (Methodist DeBakey Cardiovascular Journal)
This 62-minute webcast features a conversation about “Women and the Heart: Gender-Related Differences in Cardiovascular Care”—the focus of Issue 20.2. Led by the issue’s editor, the discussion engages the authors on emerging themes and lessons learned while researching and writing the articles. View the video at https://vimeo.com/1041140464.